Conductive Fe3O4/PANI@PTFE membrane for high thermal efficiency in interfacial induction heating membrane distillation. (November 2021) - Qing, Weihua; Hu, Zhifeng; Ma, Qingquan; Zhang, Wen
Abstract: Conventional membrane distillation (MD) undergoes interfacial temperature polarization and thus may suffer from a reduced thermal efficiency when using the hot saline water as the primary thermal driver. To address this issue, this study employed a conductive Fe3 O4 /polyaniline (PANI) coated polytetrafluoroethylene (Fe3 O4 /PANI@PTFE) membrane to achieve local interfacial heating under electromagnetic induction and promote the thermal efficiency of direct-contact MD (DCMD). Induction-responsive Fe3 O4 nanoparticles were dispersed in a conductive PANI polymer matrix that binds to the hydrophobic porous PTFE membrane by spray coating. Dispersing Fe3 O4 nanoparticles in a conductive PANI polymer matrix doubled the heating efficiency (2.0 °C s −1 ) than directly dispersing Fe3 O4 nanoparticles onto PTFE without PANI (1.1 °C s −1 ). This enhanced heating efficiency is ascribed to the formation of multiple conductive pathways or eddy current channels via the conductive polymer networks. A parametric study of the DCMD performance revealed that the permeate flux increased from 0.7 to 3.4 L m −2 h −1 with the increase of the coolant flow velocity (1.4–22.9 cm min −1 ) and induction power (0.9–3.6 kW). However, increasing the feed (3.5 wt% NaCl solution) flow velocity (1.4–8.6 cm min −1 ) significantly reduced the permeate flux from 5.0 to 1.6 L m −2 h −1 due to the insufficient time of water/membrane contact for mass transfer. Moreover, thermal and mass transport processes at the induction-heated membrane interface were analyzed by finite element analysis (FEA), which matched well the experimental results and determined the thermal efficiency up to 88% as opposed to the reported levels (20–58%) for the conventional DCMD. Our study laid additional foundation for induction-heating DCMD by devising new composite membrane materials and new interfacial thermal and mass transfer mechanisms. Graphical Abstract: ga1 Highlights: Conductive Fe3 O4 /PANI@PTFE membrane prepared for interfacial induction heating DCMD. Dispersing Fe3 O4 in conductive PANI polymer enabled higher induction heating rate. The interfacial heating membrane eliminated temperature polarization. The interfacial heating membrane exhibited unparalleled thermal efficiency of up to 88%. COMSOL simulated the mass/heat transfer of this interfacial heating DCMD.